Supercondutividade : uma abordagem para o ensino médio centrada em vídeos-experimentos - Peres, Marcelo da Silva (2021)
The present work entitled Superconductivity - an approach to high school centered on video-experiments, aimed to prepare the didactic material on the theme and its implementation, in the remote teaching modality, for graduates of the Professional National Master's Program in Physics Teaching at the Universidade Federal de Mato Grosso (UFMT) of the Campus - Araguaia, and also of graduate students from the this campus. The theme Superconductivity, which is quite complex and broad, is not included in the curriculum of high school Physics subjects, which leads to a great gap between the content seen in the classroom and the reality of science and technological applications. As a way to remedy this deficiency, we elaborated a detailed material that brings from the review of important concepts to the understanding of Superconductivity, such as a historical survey, the different types of superconductors, main effects and a first explanation of success (the BCS theory). Our methodology was centered on video-experiments on several experiments involving the phenomenon of superconductivity, in an attempt to make up for the absence of real experiments. The results obtained allow us to infer that students have a good learning about the theme and unanimously recognize the importance of videos-experiments in their learning processes.